AB0542 Do Age-Related Variations Remain in Henoch-Schölein Purpura Currently?. (15th July 2016) - Rey, F.; Rubio, A.; Peña, C.; Bonilla, C.; Cruz, A.; Collado, P.
Abstract : Background: Henoch-Schölein purpura (HSP) is a generalised vasculitis characterised by various combinations of skin, joint, gastrointestinal and renal involvement. The diagnosis HSP is based on clinical and histological features. HSP can occur at any age, but is most common in childhood. The etiology remains unknown, although it is quite common upper respiratory tract (URT) infections as a precedent. Objectives: To describe the prevalence of the clinical manifestations in adults and children at the time of diagnosis of HSP. Methods: A retrospective study of the case records of all admitted patients identified by the HSP diagnosis in the Hospital Universitario Severo Ochoa (Madrid, Spain) between January 1976 and June 2015 was undertaken. Classification criteria proposed by Michel et al were used for the diagnosis - including age <20 years at onset (1). Demographic, clinical and laboratory data at the time of diagnosis of the patients with HSP were extracted from their clinical records according to a specifically designed protocol and stored in a computerized file. Continuous data were described as mean and standard deviation (mean, SD), or median and interquartile range (IQR) and categorical variables as percentages. Means and incidence rates were compared using the Student t test. To compare categorical data we performed the chi-square test. Results: We identified 51 patients, mainly male (64.7%), with a median age at the onset of symptoms of 18 (IQR 13–41) years old. Thirty nine were younger than 20 years old. In 51% a history of URT infection before the onset of HSP was found, particularly in children (56.4%), without statistical significance (p=0.19). Palpable purpura was the initial manifestation of the disease in all patients. Differences in the distribution of cases by joint and abdominal manifestations between adults and children were not statistically significant. Joint involvement was presented in 66.7% (34 patients), where arthritis was recorded up to 41.2%, mostly children having arthritis in 84.21% (p=0.5). Abdominal manifestations were presented in 60.8% (47% adults and 13% children) (p=0.8). Renal manifestations were hardly recorded at onset, whereas up to 66.7% had no renal involvement described (31 children and 3 adults) (p=0.001). Hematuria and proteinuria were observed in 3.9% and 2% of the study population respectively, while the association of both renal manifestations was observed in 21.6%. Conclusions: Although the simple size is small, our study shows several differences at the onset of HSP between adults and children. The disease is observed predominantly in childhood, where joint involvement was frequent. Renal involvement, generally manifested as hematuria either isolated or in association with proteinuria, constitutes the most serious feature of HSP in adulthood. References: Michel BA, Hunder GG, Bloch DA, Calabrese LH. Hypersensitivity vasculitis and Henoch-Schonlein purpura: A comparison between the 2 disorders. J Rheumatol 19: 721–8, 1992 Disclosure of Interest: None declared